Objectives of Extension Education: An Analysis of Perception of KVK Professionals - Singh, Prashish; Jirli, Basavaprabhu; Ghadei, Kalyan; Roy, Priyanka; Kumari, Jagriti (Indian Journal of Extension Education, 2023)
Krishi Vigyan Kendra provides training to various stakeholders as a means of delivering technology. As a profession, the KVK professionals should have the holistic understanding and appropriate perception towards objectives of extension education. The objective of study was to analyze the perception of KVK professionals towards objectives of extension education. The study was conducted during March-August, 2021 using structured questionnaire. The sample of the study included 150 KVK scientists from 145 KVKs spread over 24 states and Union territories. The study assessed the perception of the KVK professionals towards the objectives of Extension. This Perception towards objectives was measured by using 5 point continuum on Liker scale with the help of 34 statements. The objective “Communicating the research information that is useful for economic and practical purposes” scored first rank with 66.67 weighted mean score and also revealed that majority of KVK professionals were having favorable Perception regarding objectives (74.67%) of extension followed by equal number of respondents (12.66%) were having both highly favorable and unfavorable perceptions towards objectives of extension. Additionally, it was shown that information seeking behaviour had positive and significant relationship with the perception of KVK professionals regarding objectives of extension education. Step-wise regression model revealed that information seeking behavior contributed about 2.70 per cent of total of variances in perceptions toward objectives of extension. Hence, it can be concluded that KVK professionals need to have favourable perception towards objectives of extension for executing mandates of KVK more successfully.
Keywords: Objectives of extension; Perception; Krishi Vigyan Kendra; Information seeking behaviour; Extension service provider; Economic and practical utility